Kecerdasan Budaya Mahasiswa Calon Konselor - Latif, Suciani (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
The aim of this study is to produce a profile of cultural intelligence of student. Participants are students of Teacher Education Program-Counseling (PPG-BK) SM3T Makassar State University. Number of participants as many as 16 students consisting of 13 women and 3 men. The instrument used is the scale of cultural intelligence which is the result of adaptation and modification of Cultural Intelligence Scale developed by Early and Ang (2003). Data analysis used descriptive data analysis to describe the level of cultural intelligence of students. The results of this study indicate that students' cultural intelligence are mostly located in the high category. On average the results of each dimension is found that the dimensions of CI Metaconitive have the highest rates, followed by CI Motivation, and the lowest CI Cognitive Behavior. Discussion, limitations and recommendations discussed in the study.